The water-retaining polymer improves the seedlings quality of native forest species in a nursery - Stahl, Júlia Luiza; Machado Araujo, Maristela; Griebeler, Adriana Maria; Turchetto, Felipe; Oliveira dos Santos Correa, Ulysses (Bosque (Valdivia), 2022)
Forest nurseries that produce native species seedlings need to make heigh forestry diversity available to supply the demands of forest ecosystem recovery projects. In this way, understanding the behavior of different species and improving production technology improve management and reduce losses. We here studied the effect of the water-retaining polymer addition to the substrate on the performance of three native species grown under nursery conditions. The experimental design was completely randomized with a factorial scheme. Survival, morphological and physiological attributes of seedlings were investigated. In general, it was observed that studied species proved to be suitable for the subculturing technique, with high survival despite of hydrogel negative influence on this variable in seedlings. On the other hand, the use of water-retaining polymer improved growth in height, stem diameter and seedlings quality, demonstrating to be a viable strategy in native seedlings production in a nursery.